Association Between Multidimensional Social Participation and Hypertension Among Middle‐Aged and Older Adults in China: A Cross‐Sectional Analysis From the China Health and Retirement Longitudinal Study - Zilong Shao; Yu Chen; Sheng Sun; Mengping Wang (The Journal of Clinical Hypertension)
ABSTRACT Hypertension is a significant public health issue, particularly among middle‐aged and older adults. This study investigated the impact of multidimensional social participation, including its diversity and frequency, on hypertension in this population in China, with a focus on urban–rural differences. Using data from the 2015 China Health and Retirement Longitudinal Study (CHARLS), which included 12 165 participants aged 45 and older, social participation was categorized by diversity (e.g., voluntary activities, Mahjong, cards, chess, or other clubs) and frequency. Hypertension was determined based on self‐reported diagnoses, medication use, and blood pressure measurements. Logistic regression analyses, adjusted for demographic and health‐related factors, revealed that more diverse social participation was associated with lower hypertension rates (OR = 0.718, 95% CI = 0.612, 0.840). Participating more than once a week also correlated with reduced hypertension risk (OR = 0.877, 95% CI = 0.803, 0.958). Specific activities, such as volunteering, internet use, and Mahjong, were notably protective against hypertension. Subgroup analyses highlighted urban–rural disparities, with differing impacts of social participation observed. However, interaction analyses showed that urban–rural residency did not significantly modify the relationship between social participation and hypertension. These findings emphasize the role of social participation in mitigating hypertension risk among middle‐aged and older Chinese adults, and underscore the need for targeted public health strategies to address urban–rural disparities and promote social participation.